Rethinking the role of english language teaching in Europe - Cavalheiro, Lili (2017)
This chapter reflects on the teaching of English as a foreign language (TEFL), considering the presence of English in continental Europe and its unique linguistic scenario. Following Berns (1995), it will be analyzed the three central features concerning its specificity: the multiple roles of English, the nativization or Europeanization process, and the shared patterns of acquisition and use. It is only by first understanding the various functions English has taken on in our society and how its speakers are adapting it to their needs that we can at a second moment reflect on the pedagogical implications associated with English Language Teaching (ELT). It also focuses on the dichotomy ELF and EFL, emphasizing on the importance of an ELF approach where English as a language for supranational communication is emphasized, with stress on intercultural communication and language awareness, in which communication strategies and accommodation skills are essential. By doing so, the notion of plurilingualism through English will reinforce and contribute to the idea that national and European identities are not monolithic.